Negotiating Sharia and Power: Political Dynamics behind the Drafting of the Qanun on Ahwal Al-Syakhsiyyah in Aceh - Makinara, Ihdi Karim; Idami, Zahratul; Rinaldi, Yanis; A. Rani, Faisal (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2025)
This article explores the political dynamics behind the legislative process of the Qanun on Ahwal al-Syakhshiyah in Aceh, a province with special autonomy to implement Islamic law in Indonesia. Rather than focusing solely on the substance of the qanun, this study investigates the complex interplay of power, ideology, and institutional interests during its formulation. The main research question addressed is: How do political, religious, and institutional actors shape the legislative process of Islamic family law in Aceh? Using a socio-legal approach and political legal theory, this article analyzes the roles of key actors such as the Aceh House of Representatives (DPRA), the Ulama Consultative Council (MPU), the provincial executive, civil society, and the central government. The study reveals that the legislative process is not merely normative or religious in character, but is deeply embedded in political contestation, ideological negotiation, and regional–national power dynamics. This article contributes to the discourse on Islamic legal politics by demonstrating how sharia-based legislation in autonomous regions is shaped by broader negotiations of authority and legitimacy.